The Poet as Cyber-Linguistic Programmer of Her Age: McCaffery. Issue 3 (September 2021) - Sussman, Henry
Abstract : This article posits that Steve McCaffery's radical poetico-graphic experimentation, from the 1970s through to the present day, is an exemplary site at which innovations in poetics and technology converge. At stake in McCaffery's multifaceted achievement are, among other issues: the composition of the poetic page as a screen, with its integral design and integrity; the transition between analog and digital print organisations, in thinking as in technology; the history of printing, as evidenced by his deployment of the transitional technology of the IBM Selectric typewriter in the composition of images as well as texts; and the notion that graphics (figures, cartoons, maps, and charts – with and without words) can be imbued with the figuration and articulatory nuance characteristic of verse. Throughout McCaffery's double compilation volume, Seven Pages Missing (2000 and 2002), the poet explicitly registers the transformations in communications, information, and technology that he could not help but experience around him. His poetic experiments are concurrent with luminous introductions to the cybernetic universe furnished by the likes of Anthony Wilden and Douglas Hofstadter. McCaffery's experiments, in their boldness and scope, also shed light on the venerable, ongoing cultural play between analog and digital: not period-specific or bound to particular technologies of calculation, communications, and reproduction.